Implementation Of Audio-Visual Media In Stimulating Moral And Religious Values Abilities In Group B At Nurul Iman Kindergarten In The 2024/2025 Academic Year - Fauziah, Laylatul; Eliyana, Eliyana; Fitriani, Maulida Arum (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. Stated that this study aims to describe the implementation of audio-visual media in stimulating moral and religious skills in group B at Nurul Iman Kindergarten, Karang Sobor, Tanjung. This research is a qualitative study with a case study approach. Data collection techniques used in this study included observation, interviews, and documentation. Information was collected from the principal, class teachers, and assistant teachers. The data analysis technique used in this study involved several stages, including 1) Data Collection, 2) Data Reduction, 3) Data Presentation, and 4) Conclusions.The results of this study reveal that the implementation of audio-visual media in stimulating moral and religious values has been designed and implemented to instill moral and religious values so that the school can achieve its goals. To be more effective, an evaluation is conducted so that the school can identify shortcomings and areas for improvement.